Dampak Toxic Relationship Terhadap Kesehatan Mental - Ageng Saepudin Kanda; Ranti Kivania (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
In establishing a good relationship with family, friends, partners, recognize that the relationship tends to be toxic or not, not infrequently the relationship already has toxic indications but has not realized and even still survives in the toxic relationship. Researchers aim to determine the impact of toxic relationships, whether in a close environment can trigger damage to mental health. The researcher's method uses a mixed method with 11 respondents, the researcher obtains by asking questions through interviews and questionnaires, the results show that in family relationships, friends, and couples, toxic relationships can occur which have a negative impact on psychological and physical health. The researcher's conclusion is that it is good for someone if they already have one of the characteristics of a toxic relationship indicator to immediately leave the toxic relationship and love themselves to maintain mental health.